New Developments in College Transfer. ERIC Higher Education Research Currents - Trivett, David A.; ERIC Clearinghouse on Higher Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
The issues and problems associated with transferring from one educational institution to another have existed for some time. This article reports on developments that may increase the flexibility and improve the efficiency of college-university transfer. Following a discussion of the numbers, types, and problems of transfer students, emphasis is placed on efforts to facilitate the transfer process. These efforts include: (1) institutionalization of the process through committees, conferences, and periodic reports; (2) state transfer policies; and (3) private college transfer programs. Additional areas of concern that accompany an awareness of the transfer situation are discussed including: the special needs of military students and transfer of credit of vocational, technical, or career courses from a 2-year or proprietary institution. (Author/MJM)
Availability: Publications Department, American Association for Higher Education, One Dupont Circle, Suite 780, Washington, D.C. 20036 ($0.40).
Sponsoring Agency: National Inst. of Education (DHEW), Washington, DC.
Sponsoring Agency: American Association for Higher Education, Washington, DC.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: College Transfer Students; Colleges; Educational Needs; Higher Education; Transfer Policy; Transfer Programs; Transfer Students; Transfers; Universities; Reference Materials, Bibliographies